Religion in Eastern Europe : Christians associated for relations with East Europe - Christians Associated for Relationships with Eastern Europe (U.S.); Associated Mennonite Biblical Seminary. (Princeton Theological Seminary, 1993)
Continues: Occasional papers on religion in Eastern Europe, ISSN 0731-5465.Published: Elkhart, Ind. : Associated Mennonite Biblical Seminary, Feb. 2006-.